2018
DOI: 10.1371/journal.pone.0190039
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin attenuates motor neuron programmed cell death in a burn animal model

Abstract: Burn-induced neuromuscular dysfunction may contribute to long-term morbidity; therefore, it is imperative to develop novel treatments. The present study investigated whether erythropoietin (EPO) administration attenuates burn-induced motor neuron apoptosis and neuroinflammatory response. To validate our hypothesis, a third-degree hind paw burn rat model was developed by bringing the paw into contact with a metal surface at 75°C for 10 s. A total of 24 male Sprague–Dawley rats were randomly assigned to four gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…In neonatal rats, delayed EPO administration stimulated oligodendrogenesis and attenuated white matter damage in hypoxic/ischemic brain injury (19). Furthermore, EPO attenuated inflammatory response by decreasing cyclooxygenase 2 and inducible nitric oxide synthase, suppressing microglial activation and inhibiting autophagy activation in burn-induced motor neuron neuroinflammation (20).…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal rats, delayed EPO administration stimulated oligodendrogenesis and attenuated white matter damage in hypoxic/ischemic brain injury (19). Furthermore, EPO attenuated inflammatory response by decreasing cyclooxygenase 2 and inducible nitric oxide synthase, suppressing microglial activation and inhibiting autophagy activation in burn-induced motor neuron neuroinflammation (20).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed EPO improved rat heart fibrosis through the PI3K/Akt/TLR4 pathway to suppress the release of mediators such as TGF-β1, proinflammatory cytokines, and matrix metalloproteinase [58]. EPO exerts neuroprotective effect in neurodegenerative diseases [104], ischemic brain injury [105,106], spinal cord injury [107] and motor neuron death post-burn [69]. EPO has also been found to improve muscular dysfunction in various experimental models, possible through increasing autophagy as well as decreasing apoptosis in type 2 diabetic skeletal muscles [65], reducing apoptosis in a crushing injury model [108] and preventing cancer-induced muscle alteration [67].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, two groups were treated with daily or weekly EPO as scheduled. Our preparation of EPO and the dosage we used were based on our previous study [69]. Four weeks (W4) after burn, blood samples were collected to measure red blood cell (RBC) mass by an autoanalyzer (Bayer ADVIA 2120).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal cell death is closely associated with apoptosis, and many apoptosis factors can be observed in neurodegenerative disease. Previous studies have reported that inhibition of apoptosis can help protect damaged neuronal cells (Balez et al., ; Chuang et al., ; Wu et al., ). Neuroprotective effects related to apoptosis are commonly demonstrated using PI or Hoechst 33342 staining, Annexin V/PI staining, immunochemistry, calcium concentration, and western blot.…”
Section: Determination Of Neuroprotective Effect Of Peptides/hydrolysmentioning
confidence: 99%